'20 tins of Stella for a fiver': The making of class through Labour and Coalition government alcohol policy. (October 2014) - Haydock, William
Alcohol use in the UK has been a key concern to both the Labour and Coalition governments, and commands considerable attention in the media and academic discussions. This article analyses how recent government policy discussions have defined particular forms of drinking as problematic, and how these definitions and associated policy initiatives can be seen as part of a wider symbolic economy through which people come to be valued differently, incorporating ideas of economic, cultural and social capital. Therefore, I argue that government policies and discussions of drinking are a key way in which class is constituted in contemporary Britain.